1D and 2D NMR studies of BENZYL O–VANILLIN - Al–Douh, Mohammed Hadi; Abdul Hamid, Shafida; Osman, Hasnah (Universitas Gadjah Mada, 2008)
The reaction of o–vanillin A with benzyl bromide B2 in acetone as the solvent and K2CO3 as a base in the presence of tetra–n–butylammonium iodide (TBAI) as catalyst formed benzyl o–vanillin, C. The complete assignments of C using PROTON, APT, DEPT–135, COSY, NOESY, HMQC and HMBC NMR in both CDCl3 and acetone–d6 are discussed, and the coupling constants J are reported in Hertz (Hz).